ISLAMIC EDUCATION CURRICULUM MODEL BASED ON CHARACTER AND SPIRITUAL INTELLIGENCE FOR GENERATION Z - Irfan Syahroni, Muhammad; Sunardi, Sunardi (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The idea of reconstructing the Islamic education curriculum has resurfaced in line with the phenomenon of digitalization for Generation Z, who are experiencing a loss of moral and spiritual values. Purpose: This study aims to analyze and offer a character-based and spiritually intelligent Islamic education curriculum design for Generation Z students. Method: It uses a qualitative approach with library research through searching and analyzing literature related to the main research theme. Result: The results of this study indicate that the Islamic education curriculum needs to integrate Islamic character and spiritual values with Western thought. Learning should be based on students' spiritual and social experiences and utilize digital media in a guided manner. The evaluation process must be based on observations of students' social behavior and self-transformation. Conclusion: Thus, the Islamic education curriculum will be able to produce a generation that is not only intellectually intelligent but also possesses emotional and spiritual intelligence. Therefore, the results of this study are expected to provide theoretical implications for a new paradigm of Islamic education curriculum transformation based on science, values, and technology.